Analisis Strategi Pengembangan Tenun Ikat Sumba Oleh Maestro Atau Penenun Sebagai Bentuk Ekspresi Budaya Di Provinsi Nusa Tenggara Timur - Sa’diyah, Chalimatus (CV. Multi Kreasi Media, 2024)
This study aims to explore development strategies for Sumba ikat weaving within the context of traditional craftsmanship and its potential as an export item. Sumba ikat weaving is a cultural heritage with high value both in terms of its production techniques and its diverse motifs. This research employs a quantitative method with data collected through questionnaires and observations of Sumba weaving craftsmanship. The analysis results indicate that the development strategies for Sumba ikat weaving include preserving traditional techniques, leveraging local community potential, and enhancing exhibition activities to attract wider public interest. Additionally, collaboration with third parties, innovation in production, and effective promotion are necessary to maintain market interest and increase demand. The findings of this study reveal that despite challenges in development, the potential for Sumba ikat to become an export product and support the local economy is substantial. Community involvement in promotional and preservation efforts is crucial for ensuring the sustainability and growth of this industry. In conclusion, public interest in traditional Indonesian textiles, particularly Sumba ikat, remains high and shows great potential for further development.